2008
DOI: 10.1364/oe.16.010900
|View full text |Cite
|
Sign up to set email alerts
|

Phase imaging of cells by simultaneous dual-wavelength reflection digital holography

Abstract: We present a phase-imaging technique to quantitatively study the three-dimensional structure of cells. The method, based on the simultaneous dual-wavelength digital holography, allows for higher axial range at which the unambiguous phase imaging can be performed. The technique is capable of nanometer axial resolution. The noise level, which increases as a result of using two wavelengths, is then reduced to the level of a single wavelength. The method compares favorably to software unwrapping, as the technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…In particular, we present dynamic imaging data of semiconductor structures while being etched; epi-DPM reveals quantitatively the etch rate at each point in the image and each moment in time. We found this rate to vary significantly versus position and time with typical values in the range of 0-8 nm s 21 . Finally, we show that photochemical etching can be used in combination with epi-DPM imaging to controllably vary the etch rate across the sample and thereby fabricate 'gray-scale' structures, e.g., microlenses.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…In particular, we present dynamic imaging data of semiconductor structures while being etched; epi-DPM reveals quantitatively the etch rate at each point in the image and each moment in time. We found this rate to vary significantly versus position and time with typical values in the range of 0-8 nm s 21 . Finally, we show that photochemical etching can be used in combination with epi-DPM imaging to controllably vary the etch rate across the sample and thereby fabricate 'gray-scale' structures, e.g., microlenses.…”
Section: Introductionmentioning
confidence: 77%
“…To exploit this feature, we imaged the topography of an n1 GaAs wafer while being etched with a solution of H 3 PO 4 :H 2 O 2 :H 2 O (see Supplementary Information for details on the processing steps). 23 We acquired 400 frames at 8.93 frames s 21 , for a total of 44.8 s. Our epi-DPM movie (Supplementary Movie) revealed that it took approximately 10 s for the etchant to diffuse into the field of view and begin etching. The montage in Figure 3a indicates the spatial inhomogeneity and the time evolution of the etching process.…”
Section: Monitoring Nanoscale Topography During Etchingmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, as a result of new advances in light sources, detector arrays and computing power, quantitative phase imaging (QPI), in which optical path-length delays are measured at each point in the field of view, has become a very active field of study 9 . Whether involving holographic or non-holographic methods 10-16 , QPI presents new opportunities for studying cells and tissues non-invasively, quantitatively and without the need for staining or tagging [17][18][19][20][21][22][23] . Projection tomography using laser QPI has made use of ideas from X-ray imaging and enabled three-dimensional imaging of transparent structures [24][25][26] .…”
mentioning
confidence: 99%